2007
DOI: 10.1128/aem.02016-06
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Novel Small Antimicrobial Protein from the Seeds of Motherwort ( Leonurus japonicus ) Confers Disease Resistance in Tobacco

Abstract: Medicinal plants are valuable resources of natural antimicrobial materials. A novel small protein with antimicrobial activities, designated LJAMP1, was purified from the seeds of a medicinal herb, motherwort (Leonurus japonicus Houtt). LJAMP1 is a heat-stable protein with a molecular mass of 7.8 kDa and a determined isoelectric point of 8.2. In vitro assays showed that LJAMP1 inhibits the growth of an array of fungi and bacteria. The hyphal growth inhibition by LJAMP1 was more evident against hyphomycete fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…Hence an attempt is made to explore the possible antimicrobial peptides generated through the medicinal plant. In previous studies, A 7.8 kDa of antimicrobial protein was isolated from the Seeds of Motherwort [28]. Similar to our study we found 35 kDa of protein isolated from Murraya Koenigii [29].…”
Section: Discussionsupporting
confidence: 78%
“…Hence an attempt is made to explore the possible antimicrobial peptides generated through the medicinal plant. In previous studies, A 7.8 kDa of antimicrobial protein was isolated from the Seeds of Motherwort [28]. Similar to our study we found 35 kDa of protein isolated from Murraya Koenigii [29].…”
Section: Discussionsupporting
confidence: 78%
“…Postharvest losses are estimated to range from 10% to 30% per year despite the use of modern storage facilities and new crop conservation techniques Recently the use of antimicrobial peptides, naturally produced by a variety of microorganisms and plants, was proposed for bioengineering and crop protection applications [6][7][8][9]. The decrease of susceptibility to pathogen infection as a result of transgenic production of antimicrobial agents in plants has been reported for thionins [10,11], lipid transfer proteins (LTPs) [12], defensins [13,14], snakins [15,16], and Leonurus japonicus antimicrobial protein (LJAMP1) [17], which have been isolated from such plants as: Vigna unguiculata, Arabidopsis thaliana, Medicago sativa, Raphanus sativus, Solanum tuberosum and Leonurus japonicus. The natural production of such antimicrobial proteins in plants is thought to be part of the constitutive or inducible defense mechanisms against pathogens acquired by plants in the course of evolution [18].…”
mentioning
confidence: 99%
“…The decrease of susceptibility to pathogen infection as a result of transgenic production of antimicrobial agents in plants has been reported for thionins [10,11], lipid transfer proteins (LTPs) [12], defensins [13,14], snakins [15,16], and Leonurus japonicus antimicrobial protein (LJAMP1) [17], which have been isolated from such plants as: Vigna unguiculata, Arabidopsis thaliana, Medicago sativa, Raphanus sativus, Solanum tuberosum and Leonurus japonicus. The natural production of such antimicrobial proteins in plants is thought to be part of the constitutive or inducible defense mechanisms against pathogens acquired by plants in the course of evolution [18].…”
mentioning
confidence: 99%
“…A 5-kDa peptide, Pe-AFP1, from passion fruit (P. edulis seeds) homologous to storage 2S albumins, inhibited development of the ilamentous fungi A. fumigatus, F. oxysporum, and Trichoderma harzianum, with IC50 values of 40, 34, and 32 μg/mL, respectively, but had no effect on C. albicans, Paracoccidioides brasiliensis, and Rhyzoctonia solani (Pelegrini et al 2006). Peptide LJAMP1 from motherwort (L. japonicus) seed extract with sequence homology to 2S albumins expressed antifungal activity against A. alternata, C. personata, and A. niger (Yang et al 2007). A heterodimeric 11.5-kDa Passiflora alata antifungal protein named Pa-AFP1, with marked homology to 2S albumins and composed of 4.5-and 7-kDa subunits, retarded the growth of the fungus C. gloeosporioides, but was inactive toward bacteria and yeasts (Ribeiro et al 2011).…”
Section: S Albumin Proteinsmentioning
confidence: 96%